Effect of biofertilizers (Azotobacter and Azospirillum) alone and in combination with reduced levels of nitrogen on post harvest quality of cauliflower Cv. Snowball-16 - Sable, P. B. (INTERNATIONAL JOURNAL OF AGRICULTURAL SCIENCES, 2025)
An experiment was conducted during Rabi season of 2004-05 involving three levels of nitrogen (0, 100 and 75% nitrogen) with four levels of biofertilizers (no inoculation, Azospirillum, Azotobacter and Azotobacter + Azospirillum). Out of the twelve treatment combinations the best treatment was 75 per cent nitrogen (120 kg ha-1) + Azotobacter + Azospirillum which showed significant increase in ascorbic acid content in curd (87.00 mg/100g), total nitrogen content in plant (2.98%), protein content in curds (18.62%) and compactness of curd (97.39%).